(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Mediation is increasingly recognized as an effective alternative dispute resolution (ADR) mechanism in European countries. This article examines mediation practices across Europe, highlighting legislative frameworks, procedural approaches, and effectiveness. Using a comparative legal analysis, this study identifies key trends, challenges, and best practices in mediation. The findings reveal significant variations in mediation adoption and implementation, influenced by legal traditions and cultural factors. The study concludes with recommendations to enhance mediation’s role in European legal systems.